Determinants of Social Impact Through Safety Culture in Technical Organizations - Christian Schachtner; Adam Jabłoński; Marek Jabłoński (Corporate Social Responsibility and Environmental Management, 2025)
The aim of the article is to show the results of research on whether safety culture is the social impact of technical organizations. It is important to fix determinants of social impact through safety culture in technical organizations. Positive safety culture is the result of consistent management actions aimed at both the inner workings of the company and its external environment. A safety culture should ensure that the risks associated with operational processes are mitigated in the context of adverse events such as disasters, accidents, incidents, law infringements, and so forth. Safety is a social good, which is the foundation and priority of people's quality of life. Meeting the safety needs of society is the task of responsible managers of technical organizations. The proposed analytical and research model has been used to analyze the factors shaping a safety culture in the context of their importance in the implementation of social impacts. The Vester and AHP methods were used to assess the impact of defined individual factors of shaping a safety culture and to determine the ranking of factors with the highest weights. The article is a step towards defining the processes of shaping a safety culture of technical organizations in the context of their social impact.
Keywords: 650; safety culture; social impact; technical organization